Protective effects of resveratrol on acute kidney injury in rats with sepsis - Luo, Cong-Juan; Luo, Feng; Bu, Quan-Dong; Jiang, Wei; Zhang, Wei; Liu, Xue-Mei; Che, Lin; Luan, Hong; Zhang, Hui; Ma, Rui-Xia; Sun, Jian-Ping; Xu, Yan (Biomedical papers, 2020)
Aim: To evaluate the protective effects of resveratrol on acute kidney injury (AKI) in septic rats. Methods: A septic rat model was established by cecal ligation and puncture (CLP). A total of 108 male Sprague Dawley rats were randomly divided into an observation group, a 6 h resveratrol intervention group and a 12 h resveratrol intervention group. Then each group was subdivided into Sham, Sham + Res, CLP and CLP + Res groups. After surgery, the survival and morphological changes in kidney tissues were observed. Serum creatinine and urea nitrogen levels, expression of GRP78, BiP, IRE1 and p65 in kidney tissues, and serum levels of TNF-α, IL-1β, IL-6 and IL-10 were investigated. Results: The survival rate of CLP + Res group (75.00%) significantly exceeded that of the CLP group (41.67%) (P<0.05). At postoperative 12 h, resveratrol significantly decreased serum creatinine and urea nitrogen levels (P<0.05). Resveratrol evidently relieved renal tubular swelling and luminal narrowing in CLP rats, and significantly reduced the high expressions of GRP78, BiP, phosphorylated IRE1 and p65 proteins (P<0.05). P65 was mainly located in the cytoplasm of Sham, Sham + Res and CLP + Res groups, and in the nucleus of the CLP group. At postoperative 12 h, resveratrol significantly reduced serum levels TNF-α, IL-1β and IL-6 in CLP rats (P<0.05), whereas elevated that of IL-10 (P<0.05). Conclusion: Resveratrol significantly decreased the mortality rate of septic rats and alleviated AKI, probably by attenuating endoplasmic reticulum stress, inhibiting activation of the NF-κB pathway and mitigating the inflammatory response.
Keywords: resveratrol; sepsis; acute kidney injury; endoplasmic reticulum stress; inflammatory response